2010
DOI: 10.1097/ijg.0b013e3181ca7acf
|View full text |Cite
|
Sign up to set email alerts
|

Spectral-domain Optical Coherence Tomography Measurement of Macular Volume for Diagnosing Glaucoma

Abstract: Selective measurement of the GCC layer by SD-OCT improves diagnostic performance of the macular structural analysis for glaucoma diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
76
1
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(85 citation statements)
references
References 17 publications
6
76
1
2
Order By: Relevance
“…6,11,14,15,[17][18][19][20][21] In such investigations, for the best performing RNFLT and GCC parameters of the RTVue-100 OCT, the area under the receiver operating characteristic curve varied between 0.900 and 0.971. [17][18][19][20][21] Other authors using other Fourier-domain OCT systems reported on similar values. 6,15 These results suggest that under pre-defined circumstances the diagnostic accuracy of Fourier-domain OCT technology is somewhat higher than that of time-domain OCT technology.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…6,11,14,15,[17][18][19][20][21] In such investigations, for the best performing RNFLT and GCC parameters of the RTVue-100 OCT, the area under the receiver operating characteristic curve varied between 0.900 and 0.971. [17][18][19][20][21] Other authors using other Fourier-domain OCT systems reported on similar values. 6,15 These results suggest that under pre-defined circumstances the diagnostic accuracy of Fourier-domain OCT technology is somewhat higher than that of time-domain OCT technology.…”
Section: Discussionmentioning
confidence: 99%
“…OCT instruments employing the Fourier-domain technology have significantly higher resolution and scan speed, improved image segmentation and better measurement reproducibility compared with the timeFdomain OCT. [1][2][3][4][5][6] Though the technology is new, information on the diagnostic accuracy of the different Fourier-domain OCT instruments to detect glaucoma of different severity, is increasing. 5,6,[13][14][15][16][17][18][19][20][21] The RTVue-100 OCT (Optovue Inc., Fremont, CA, USA) is one of the new commercially available Fourier-domain OCT instruments. [1][2][3][4][17][18][19][20][21] Its axial resolution is approximately 5 mm and the scan speed is 26 000 A-scans per second.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…SD-OCT by its ability to measure individual layers of the retina may capture these changes in the macula, and a few recent studies with SD-OCT, in fact, have shown that the macular inner retinal (MIR) thickness measurements, which consists of the innermost 3 layers of the retina, namely the nerve fiber layer, ganglion cell layer, and the inner plexiform layer, were as good as the RNFL measurements in detecting glaucoma. [10][11][12][13][14] These studies, however, included glaucoma patients with all severities of visual field damage that might have biased the results, as the estimates of diagnostic accuracy are known to improve with the severity of disease. [15][16][17] In clinical practice, the challenge is to diagnose glaucoma in early stages and there is limited literature on the diagnostic ability of SD-OCT in early glaucoma.…”
Section: Introductionmentioning
confidence: 99%
“…In other studies, HL Rao et al, [4] in early POAG eyes and Seong et al, [13] in normal tension glaucoma eyes with early visual field damage, found comparable diagnostic abilities between average RNFL and macular parameters using the Fourier domain RTVue OCT. In few studies, Mori et al [14] , HL Rao et al [4] reported selective measurements of macula inner retinal (MIR) volume by Fourier domain OCT to have better diagnostic performance among macular parameters in early diagnosis of glaucoma. The inconsistencies in the diagnostic capabilities of macular parameters in various studies using SD OCT may be due to the fact that SD OCT can measure the GCC thickness in the centre of macular area (7×6 mm2) only, thus excluding the glaucomatous damage outside this region which might be affected in early glaucoma.…”
Section: Discussionmentioning
confidence: 99%